ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT. ADARO ENERGY TBK. PERIODE 2011 - 2017 - Niyati, Wahidah; Lubis, Iman (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
The purpose of this study is to measure the financial performance of PT. Adaro Energy, Tbk by using the EVA method, in order achieve magnitude of the creation economic value added and to see level of return desired by investors. Research method used in this study is a qualitative method and is descriptive with a quantitative approach where there are no samples or populations, because researchers are looking for problems that exist in PT. Adaro Energy, Tbk for the period of 2011 - 2017 using the method of Economic Value added (EVA) where in searching for WACC uses the CAPM approach. The results of the study are as follows: value of EVA experienced fluctuations, in 2011 showed a positive that is equal to 577,480 in 2012 showed a negative (470,427) in 2013 experienced a positive amount of 840,781 in 2014 had a negative of (1,426,963) in 2015 increased 1,983 .884 and in 2016 decreased (900,080) and in 2017 amounted to (1,348,304), this shows presumption that EVA in 2011, 2013 and 2015 occurred a value-added process for companies that could mean that there was more economic value, after company is able to pay all obligations funders or creditors according to their expectations, but in 2012,2014 and 2017 EVA shows that there is no value added process which means that company is unable to pay obligations to funders or creditors as expected value is not achieved.